2017
DOI: 10.1128/iai.00661-17
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1α Is Critical for Resistance against Highly Virulent Aspergillus fumigatus Isolates

Abstract: Heterogeneity among Aspergillus fumigatus isolates results in unique virulence potential and inflammatory responses. How these isolates drive specific immune responses and how this affects fungally induced lung damage and disease outcome are unresolved. We demonstrate that the highly virulent CEA10 strain is able to rapidly germinate within the immunocompetent lung environment, inducing greater lung damage, vascular leakage, and interleukin 1␣ (IL-1␣) release than the low-virulence Af293 strain, which germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 84 publications
(128 reference statements)
10
79
0
Order By: Relevance
“…infection biology and characterization of strains that were isolated from immunocompromised patients under different conditions have received considerable attention in recent years (24,37,47), whereas similar studies into other pathogenic Aspergillus spp. have been neglected although it is becoming apparent that non-A.…”
Section: Discussionmentioning
confidence: 99%
“…infection biology and characterization of strains that were isolated from immunocompromised patients under different conditions have received considerable attention in recent years (24,37,47), whereas similar studies into other pathogenic Aspergillus spp. have been neglected although it is becoming apparent that non-A.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 receptor deficiency results in profound susceptibility to A. fumigatus as a result of IL-1␣-mediated early (day 1) neutrophil recruitment and IL-1␤-mediated macrophage antifungal responses (46). More recently, IL-1␣ was found to be required for the elimination of highly virulent, highly germinating A. fumigatus strains (47). Likewise, we recently reported that another function of IL-1 receptor signaling during A. fumigatus exposure is the induction of IL-17A and IL-22 (32), both of which we have shown to be essential for A. fumigatus elimination from the lungs (48) (49).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on A. nidulans virulence have been carried out in CGD models (animal and cell culture) and virulence characteristics have been compared to the primary human opportunistic fungus A. fumigatus (20,21,45,46). A. fumigatus infection biology and characterization of strains that were isolated from immunocompromised patients with different conditions have received considerable attention in recent years (24,37,47), whereas similar studies into other pathogenic Aspergillus spp. have been neglected, although it is becoming apparent that non- A. fumigatus species, including cryptic Aspergillus species, also contribute to host infection and invasion (7).…”
Section: Discussionmentioning
confidence: 99%